Evaluation of the correlation between depression and physical activity among older persons with osteoporosis: a cross-sectional study - Shi, Linjun; Zhou, Xiaoping; Gao, Yueshan; Li, Xia; Fang, Ronghua; Deng, Xuexue (Frontiers in Psychiatry, 2023)
Background: Osteoporosis is a common chronic disease in older persons. Physical activity can prevent chronic diseases as well as many diseases associated with aging. Older persons often suffer from depression and other psychological problems. However, there are few studies on the correlation between depression and physical activity in older persons with osteoporosis in China.This cross-sectional study was conducted from June 1 to December 28, 2021. A total of 207 subjects who met the inclusion and were exclusion criteria were selected from the outpatient department of West China Hospital and evaluated using a self-designed demographic data questionnaire, the Self-rating Depression Scale (SDS), and the Physical Activity Scale for the Elderly (PASE). Multivariate linear regression was performed to analyze the factors affecting physical activity, and multivariate logistic regression analysis was performed to analyze the factors affecting depression. Spearman's correlation coefficients were calculated to analyze the correlation between depression and physical activity in older persons with osteoporosis.Results: A total of 173 valid questionnaires were statistically analyzed. A total of 122 (70.5%) participants were identified as having depression (SDS ≥50 points). The median depression score was 62.5(24.38), and the median PASE score was 69.29(116.64). Multivariate logistic regression 18 model results showed that physical activity and pain were the main risk factors for depression in older persons with osteoporosis (P < 0.05). Multivariate linear regression model results showed that gender, participation in social activities, activities of daily living status (ADLs), and depression status were the main risk factors associated with physical activity in older persons with osteoporosis (P < 0.05). The results of the correlation analysis showed that physical activity was negatively correlated with depression (R = -0.510, P= 0.000).We found that depression was negatively correlated with physical activity in older persons with osteoporosis in China. This means that the less physical activity there is, the more serious the depression status and having depression may result in reduced physical activity in older persons with osteoporosis. To better help older persons with osteoporosis, medical staff should give more attention to influencing factors of depression and physical activity.